In the form: ax^2+ bx +c to complete the square a = 1 is required. c = (b/2)^2 the square term is b/2 x^2 + 26x + c a = 1 so we are okay to complete the square. b = 26 c = (26/2)^2 = 13^2 = 169 finally to complete the square: x^2 + 26x + 169 = (x+b/2)^2 = (x+13)^2

## Answers ( )

c = 169

square is (x + 13)^2

Explanation:

In the form:

ax^2+ bx +c

to complete the square a = 1 is required.

c = (b/2)^2

the square term is b/2

x^2 + 26x + c

a = 1 so we are okay to complete the square.

b = 26

c = (26/2)^2 = 13^2 = 169

finally to complete the square:

x^2 + 26x + 169 = (x+b/2)^2 = (x+13)^2